ON A NEW SCHEMA OF AGRICULTURAL ZONING OF UKRAINE - Барановський, Микола (Human Geography Journal, 2015)
The necessity of elaborating a new scheme of agricultural zoning of Ukraine is proved, the analysis of the existing approaches and modern peculiarities of statistic base forming and defining agriculture specialization of certain territories is completed. Based on the analysis of sales volumes indices of nine types of agrarian products, the agriculture sectorial structure of administrative districts of Ukraine is determined. Using connectionist method, in particular Kohonen’s self-organizing maps, the grouping of administrative districts of Ukraine by the similarity of agriculture specialization is implemented. Seven types of districts (clusters), which differ in some peculiarities of agrarian sector specialization, are defined; evaluation of changes that happened in the agriculture specialization within existing agrarian-territorial zones, especially in Polissia and forest-steppe zone, is conducted; their reasons are determined. The map «Agriculture specialization of administrative districts of Ukraine», which can become the base for developing a new scheme of country’s agriculture zoning, is elaborated.